A review of the fossil record of turtles of the clade pan-chelidae - Maniel, Ignacio Jorge (2016)
Turtles of the total Clade Pan-Chelidae have a relatively poor fossil record, which is completely restricted from the Early Cretaceous to Recent of South America and Australasia. The clade is expected to have formerly inhabited Antarctica as well. The phylogenetic relationships of extant pan-chelids remain poorly resolved, notably because there are conflicting signals between morphological and molecular data. The ecology of fossil pan-chelids appears to have been similar to that of their extant relatives. A taxonomic review of the group concluded that of 45 named taxa, 22 are nomina valida, 6 are nomina invalida and 15 are nomina dubia, whereas the final 2 are rendered non-testudinate through the designation of lectotypes.